Molecular characterization of interleukin-4 and interleukin-6 in patients with type-2 diabetes mellitus in Iraq - Thamer, Dalfi Mazin Maky (Tanjong Malim, 2021)
Molecular characterization of interleukin-4 and interleukin-6 in patients with type-2 diabetes mellitus in Iraq by Thamer, Dalfi Mazin Maky